Multidecadal land cover changes: impacts on ecosystem service values in Nigeria - Okikiola M Alegbeleye; Yetunde O Rotimi; Abiodun Oyediran; Patricia Shomide; Daniel Abiodun Akintunde-Alo (Environmental Research Communications)
Nigeria has numerous natural ecosystems that significantly contribute to the livelihoods of its population. However, the country faces growing pressures from increasing population, climate change, and rapid land conversion that are poorly documented at the national and sub-national levels. As a result, the impacts of land cover changes on the ecological benefits provided by these ecosystems are vaguely understood. This knowledge gap hinders effective policy-making and sustainable management of the country’s natural resources. To this end, this study evaluated land cover changes (over 20 years) in different regions across Nigeria. Using a global land cover map that was locally and independently validated, with a global ecosystem service value (ESV), land cover dynamics and their impact on the ESV across the six regions in Nigeria were determined. Across the country, there has been a significant decrease in grassland/shrubland/rangeland, forest, and wetlands by 12.8%, 5.7%, and 4.1%, respectively. Also, the total ecosystem service value was reduced by 20 billion (US$) in two decades. Across all regions, there was a decline in forest cover and a significant increase in built-up, ranging from 36.69% in the southern region to 103.58% in the Northern region. Changes in land cover led to a decrease in ESV across all the regions except the North-East. The ESV reduced by 0.74%, 2.91%, 4.17%, 1.91%, and 1.11% in the South-East, South-West, South-South, North-West, and North-Central regions, respectively, while the North-East region had a 1.81% ESV increase in 20 years. With the exponential growth in Nigeria’s population, there is a need for policies and concerted efforts that ensure sustainable land use and mitigate climate change. This will prevent further loss of ecosystem services derived from the natural ecosystems.